THE DYNAMICS BETWEEN MACROECONOMIC INDICATORS TOWARDS ECONOMIC GROWTH AMONG ASEAN-5 COUNTRIES USING PANEL ANALYSIS - Ng Kuang Yong; Shamzaeffa Samsudin; Zalina Zainal; Gan Huey Ying (Malaysian Journal of Business and Economics (MJBE), 2024)
This study aims to identify the most appropriate model for conducting panel data analysis on the macroeconomic indicators towards the economic growth in ASEAN-5 countries. The research focuses on five countries: Malaysia, Singapore, Thailand, Philippines, and Indonesia, covering the period from 1980 to 2019. The independent variables under investigation include inflation, percentage of money supply to GDP, trade openness, and population. Three models are utilized including the common constant model, fixed effect model, and random effects model. To determine the most suitable model, the researchers employ the Redundant fixed effects test and the Hausman test for specification testing. The fixed effect model emerges as the most adequate model. The significant P-values obtained from both tests provide evidence in favor of the fixed effect model, indicating that it is the most appropriate choice for understanding the relationships between the independent variables and economic growth in the ASEAN-5 countries. The findings of the fixed effect model show that inflation and money supply are negatively and significantly related to economic growth at the 1% level. Trade openness is positively related to economic growth, but not significantly. Additionally, the population has a significantly positive relationship with economic growth.